Analisis Keungggulan Produk dalam Meningkatkan Daya Saing pada UMKM CV. Batik Tulis Prabulinggih - Waqi'atul Aqidah; M. Syamsul Hadi (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2023)
Product excellence is an important part in increasing competitiveness in the market, each product has its own advantages to be able to compete in the market, including CV. Batik Tulis Prabulinggih. This study aims to determine the superiority of the product in increasing competitiveness in CV. Batik Tulis Prabulinggih. This study uses qualitative methods, data collection methods of interviews, observation and documentation. The results of this study show that product excellence can support competitiveness in the market. Based on the results of research and discussion, it was found that product superiority in written batik can be seen from the 1) motif design; 2) durability; 3) colors and patterns;and 4) product variations on the CV. Batik Tulis Prabulinggih. The combination of motif design, colors and patterns of batik has regional characteristics of Kabupaten Probolinggo, so it has a different power from other batik. Thus, CV. Batik Tulis Prabulinggih.has product advantages that make it able to continue to exist and compete with other batik product in the market.